Seasonal changes in performance, physiological, and kinematic factors of maximal incremental swimming in elite open-water swimmers - López-Belmonte, Ó.; Ruiz-Navarro, J. J.; Baldassarre, R.; Bonifazi, M.; Arellano, R.; Piacentini, M. F. (International Journal of Sports Physiology and Performance, 2026)
Purpose: Despite the growing global prominence of elite open-water (OW) swimming, little is known about how seasonal variation influences the physiological and kinematic determinants of maximal performance. This study aimed (1) to evaluate the seasonal changes in performance, physiological, and kinematic factors in maximal incremental swimming tests in elite OW swimmers and (2) to examine the influence of physiological and kinematic factors on the maximal swimming performance.